Avaliação da dor pós-operatória e do campo visual utilizando bloqueio neuromuscular moderado e profundo em pacientes submetidos à By-Pass gástrico em Y de Roux por via laparoscópica - SILVA, Marcelo Nogueira da Cruz (2024)
Introduction: Surgical conditions in surgeries are determined mainly by the depth of neuromuscular relaxation, especially in procedures confined to a narrow field of work, such as gastrectomy with video-laparoscopic Roux-en-Y intestinal bypass. Sustained administration of deep neuromuscular blockade (DNB) significantly improves surgical conditions in robotic surgeries compared to moderate neuromuscular blockade. Additionally, using DNB may lower inflation pressures (low-pressure pneumoperitoneum), reducing postoperative pain scores. Objective: To evaluate the effect of deep intravenous neuromuscular blockades on improving surgical conditions and pain intensity after Roux-en-Y gastric bypass by laparoscopic surgery. Methodology: Randomized, double-blind clinical trial, carried out at Hospital São Domingos, in São Luís, Maranhão, Brazil, between October 2021 and December 2023. Patients were randomized to moderate or deep neuromuscular blockade. Patients received 0.6 mg.kg-1 of intravenous rocuronium before intubation. The data were tabulated and organized in Microsoft Office Excel® and analyzed in SPSS (v. 26). All statistical associations were set at significance p < 0.05. Results: 100 patients were considered eligible for the study, of which 39 individuals were excluded due to the impossibility of postoperative contact. Thus, the groups were divided into G1 (moderate blockade) with 37 patients and G2 (deep blockade) with 34 patients. We did not identify significant differences between the two groups regarding sociodemographic, anthropometric and comorbidity variables. Likewise, concerning perioperative and analgesia characteristics between patients. Pain assessment was carried out 9 times after the end of surgery, using the Numerical Assessment Scale. At none of the time points evaluated (T0h, 1h, 2h, 4h, 6h, 12h, 24h, 48h and 72h), was a significant difference observed between groups 1 and 2. There was a significant difference between the groups for 30 and 70 minutes, with values of p=0.015 and p=0.027, respectively. At other times, no statistical difference was observed between the groups. Conclusion: This study showed a statistical difference in the improvement of the visual field when using deep neuromuscular blockade when compared with moderate NMB, without, however, showing differences in the other variables evaluated.